Oral rabies vaccination of foxes in Türkiye, 2019–2022 - Orhan Aylan; Bayram Sertkaya; Anıl Demeli; Ad Vos; Sabri Hacioglu; Yeşim Tatan Atıcı; Deniz Acun Yıldız; Thomas Müller; Conrad M. Freuling (One Health)
Background: Rabies in Turkey is maintained by dogs, but following a sustained spill-over, red fox mediated rabies had spread from the Aegean region to the central part of Türkiye. During the past four years from 2019 to 2023 large scale efforts used oral rabies vaccination (ORV) to control rabies in red foxes. Here, we present the results of the largest ORV campaign on the Asian continent. Methods: ORV campaigns were carried out twice a year in spring and autumn with a targeted bait density of 20–23 baits/km2. Monitoring of ORV campaigns included the GIS-based analyses of bait distribution, the assessment of bait uptake through biomarker detection and the determination of seroconversion (sero-positivity in ELISA) in the target species collected within the vaccination area. For determination of fox rabies incidence in vaccination areas as the main indicator of the performance of the ORV campaigns, epidemiological data was obtained from the national passive surveillance program. Results: Aerial bait distribution was highly accurate, with >99 % of baits being recorded from targeted zones, thus meeting the desired bait densities. Although the overall bait uptake (28.1 %; 95 %CI: 23.2–32.8) and seroprevalance (36.3 %; 95 %CI: 30.0–43.2) were low, rabies incidence drastically decreased in ORV areas and rabies was eliminated from western and central parts of Turkey, with no reported cases in foxes from ORV areas in 2022 and 2023. Conclusions: A large-scale ORV campaign against fox rabies using high quality vaccine baits and the GIS-aided and monitored bait distribution was able to control fox mediated rabies in the western and central parts of Türkiye. Rabies control both in dogs and foxes should be expanded to cover also the eastern parts of Türkiye, to become eventually rabies free.